Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Coffee Shop Gerobak Kopi Payakumbuh - Fajri Hidayat; Hijriyantomi Suyuthie (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2024)
This research is motivated by customer complaints about visiting customer satisfaction which is influenced by price and service quality at Gerobak Kopi Payakumbuh. The research purpose was to describe the price and quality of service on satisfaction of customer and to determine the effect of these three variables. The research type used is quantitative with a clausal approach. This research was conducted at Gerobak Kopi Payakumbuh. Sampling for this research was using purposive sampling technique non probability sampling type. The type of data in this study is primary data. This instrument for research uses a questionnaire (questionnaire) which has been arranged according to a Likert scale which has been tested for validity and reliability first. This data was analyzed using the SPSS version 26.00 program. The results of the study, namely Price is included in the good enough category with a respondent achievement level of 47.76%, Service Quality by a respondent achievement level of 46.60% is included in the sufficient category and Customer Satisfaction with a respondent achievement level of 45.76% with a sufficient category. The contribution of Price (X1) and Service Quality (X2) to Satisfaction of Customer is 80.01% while the remaining 19.99% is impacted by another factors.